Ответ:
1.
а)-3
б)-19
в)15
г)3(общий корень 6,первую дробь умножаем на 2,а вторую дробь на 1.В первой дроби, числитель умножается на 2, следовательно 2×2=4.После 4-1=3)
д)
![- \frac{1}{3} - \frac{2}{5} = - \frac{5 - 6}{15} = \frac{1}{15} - \frac{1}{3} - \frac{2}{5} = - \frac{5 - 6}{15} = \frac{1}{15}](https://tex.z-dn.net/?f=%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20%20%3D%20%20-%20%20%5Cfrac%7B5%20-%206%7D%7B15%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B15%7D%20)
е)
![\frac{5}{7} \times ( - \frac{2}{3}) = - \frac{10}{21} \frac{5}{7} \times ( - \frac{2}{3}) = - \frac{10}{21}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B7%7D%20%20%5Ctimes%20%28%20-%20%20%5Cfrac%7B2%7D%7B3%7D%29%20%3D%20%20-%20%20%5Cfrac%7B10%7D%7B21%7D%20%20)
ж)
![( - \frac{4}{5} ) \div ( - \frac{2}{7} ) = ( - \frac{4}{5} \times ( - \frac{7}{2} ) = - \frac{2}{5} \times ( - \frac{7}{1} ) = \frac{14}{5} = 2 \frac{4}{5} ( - \frac{4}{5} ) \div ( - \frac{2}{7} ) = ( - \frac{4}{5} \times ( - \frac{7}{2} ) = - \frac{2}{5} \times ( - \frac{7}{1} ) = \frac{14}{5} = 2 \frac{4}{5}](https://tex.z-dn.net/?f=%28%20-%20%20%5Cfrac%7B4%7D%7B5%7D%20%29%20%5Cdiv%20%28%20-%20%20%5Cfrac%7B2%7D%7B7%7D%20%29%20%3D%20%28%20-%20%20%5Cfrac%7B4%7D%7B5%7D%20%20%5Ctimes%20%28%20-%20%20%5Cfrac%7B7%7D%7B2%7D%20%29%20%3D%20%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20%20%5Ctimes%20%28%20-%20%20%5Cfrac%7B7%7D%7B1%7D%20%29%20%3D%20%20%5Cfrac%7B14%7D%7B5%7D%20%20%3D%202%20%5Cfrac%7B4%7D%7B5%7D%20)
2.
а)1/2
б)1/2
в)1/2
3.
а)
- 5" alt="0 > - 5" align="absmiddle" class="latex-formula">
б)
![- 37 < - 9 - 37 < - 9](https://tex.z-dn.net/?f=%20-%2037%20%3C%20%20-%209)
4.
а)-18/5 ÷ 27/10= -18/5 × 10/27= -2/1×2/3= -4/3= -1 1/3
б)9/8 + 3/7 = 63+24/56=87/56= 1 31/56
в)-2,84